Managed honeybee hives and the diversity of wild bees in a dryland nature reserve - Leguizamón, Yamila (2021)
Honeybee hives may influence pollen and nectar availability in natural ecosystems, which may consequently affect wild pollinators. We studied the effects of managed honeybee hives on wild bee diversity in Villavicencio Nature Reserve (Mendoza, Argentina). We placed pan traps at increasing distances from honeybee hives to estimate wild bee abundance, richness, and composition. Wild bee abundance did not change detectably with distance to honeybee hives, although the abundance of the most common species, Arhysosage bifasciata, increased with increasing distance to the hives. Wild bee richness increased weakly with increasing distance to hives. Although wild bee composition did not change significantly with distance to the apiaries for the full data set, it changed significantly when we excluded A. bifasciata from the analyses. We found no relationship between body size and distance to the apiaries. Overall, our results indicate that managed honeybee hives had mixed effects on the wild bee assemblage in our study area. Given the relatively low hive density used in our study compared to other studies, we recommend an adaptive management strategy with continuous impact assessment.